2019
DOI: 10.1016/j.apenergy.2018.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Off-design optimisation of organic Rankine cycle (ORC) engines with piston expanders for medium-scale combined heat and power applications

Abstract: Organic Rankine cycle (ORC) engines often operate under variable heat-source conditions, so maximising performance at both nominal and off-design operation is crucial for the wider adoption of this technology. In this work, an off-design optimisation tool is developed to predict the impact of varying heat-source conditions on ORC operation. Unlike previous efforts where the performance of ORC engine components is assumed fixed, here we consider explicitly the time-varying operational characteristics of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…The net power output (Wnet) is used to indicate the ORC system's thermodynamic performance, while the net power output per unit heat exchanger area (Wnet/A) is used as an economic indicator. R245fa is considered here as the working fluid as it is a well-known fluid that has been extensively investigated in the literature and that is currently being used in many ORC systems for its good performance [16]. power while the pressure drop in the condenser causes higher backpressure in the expander and reduces power generation.…”
Section: Orc System Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The net power output (Wnet) is used to indicate the ORC system's thermodynamic performance, while the net power output per unit heat exchanger area (Wnet/A) is used as an economic indicator. R245fa is considered here as the working fluid as it is a well-known fluid that has been extensively investigated in the literature and that is currently being used in many ORC systems for its good performance [16]. power while the pressure drop in the condenser causes higher backpressure in the expander and reduces power generation.…”
Section: Orc System Performancementioning
confidence: 99%
“…Investigations on ORC technology for converting recovered waste-heat from ICEs have been conducted both computationally and experimentally [9,10], including on configuration design [11][12][13] and system optimization [14][15][16], working fluid selection by traditional pre-selection (including pure fluids [17,18] and mixtures [19,20]) and by new computer-aided molecular design methods [21][22][23] integrated into cycle optimization [24,25], expander selection and design [26,27] (including piston [28][29][30], screw [31][32][33] and rotary-vane [34] expanders), and off-design performance [35,36]. These excellent studies have enabled significant progress with the performance of ORC technology towards through careful considerations of the working fluid, key components and system parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, rotary and reciprocating types have been extensively considered. Screw and scroll machines have good robustness to fluctuating conditions [20], while reciprocating ones, which are characterized by a higher built-in volume ratio [21], can achieve more easily a higher expansion ratio and demonstrated very good off-design behavior [22]. Vane machines suffers toughly the leakages [23] due to vane chatter [24], which implies leakages across the adjacent chamber due to the lack of contact between the blade tip and stator [25].…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [26] pointed out that the efficiency of the WHR system under driving cycles was less than half of that in design condition. Chatzopoulou [27] proposed an off-design optimization tool considering the component time-varying performance, and concluded that the ORC power output was underestimated by 17% when the ORC components operated in off-design conditions without optimizing the performance. Some control strategies are necessary to ensure the normal and satisfactory operation of the system over a broad range of engine operating conditions due to the transient heat source of the engine.…”
Section: Introductionmentioning
confidence: 99%